PENGARUH PENGELOLAAN MODAL KERJA DAN LIKUIDITAS TERHADAP PROFITABILITAS PADA PT. PERKEBUNAN NUSANTARA IV REGIONAL III PEKANBARU - Guci, Lala Putri; Augustin, Jeneva (Jurnal Daya Saing, 2025)
Every company aims to increase its profitability. Working capital management and liquidity are two important factors that can affect the company's financial performance, especially in increasing profitability. The purpose of this study was to test and analyze the effect of working capital management and liquidity on profitability at PT Perkebunan Nusantara IV Regional III Pekanbaru. Working capital management is measured using cash turnover ratio, inventory turnover and working capital turnover, while liquidity is measured using cash ratio, current ratio and quick ratio. Profitability is measured using Return on Assets (ROA) as the main indicator. This research uses quantitative methods with secondary data in the form of monthly and annual financial reports of PT Perkebunan Nusantara IV Regional III Pekanbaru during the 2021-2023 period. The data analysis method used is descriptive statistical analysis, classical assumption test, multiple linear regression analysis, hypothesis testing, and determination coefficient test (R²). The results of this study are known that cash turnover has no effect on profitability. Inventory turnover has a significant effect on profitability. Working capital turnover has no effect on profitability. Cash ratio has a significant effect on profitability. Current ratio has a significant effect on profitability. Quick ratio has no effect on profitability. Based on the results of the study to increase profitability can be done by improving the management of working capital and liquidity effectively and efficiently in the company. Keywords: Working Capital Management, Liquidity, Profitability, and Return on Assets (ROA).